VALIDITAS DAN RELIABILITAS ANGKET PENYESUAIAN DIRI SISWA SMA - Winda Regita Fitriany Husaeni; Wahyu Hidayat; Wiwin Yuliani (IKIP Siliwangi, 2022)
Self-adjustment is a process carried out by students in an effort to achieve self-harmony with the environment, so that feelings such as insecurity, disappointment, a sense of wanting to isolate themselves from the environment and others as negative emotions can be removed or avoided from within. student. As above, the ability to adapt is important for every student. Therefore, a measuring instrument is needed to determine the condition of self-adjustment of the self-adjustment questionnaire students, namely using R&D development research (Research and Development) which aims to test the validity and reliability of the self-adjustment questionnaire. With research subjects class XI SMAN 2 Padalarang. And the results of the validity test of this self-adjustment questionnaire state that there are 12 valid questions and the results of the reliability test with a total of 0.453 which are categorized as moderate from 30 questions made by researchers from 25 respondents. Keywords: self-adjustment, validity, reliability